Rock Mass Characterisation Of Tunnel Face Using Image Analysis Technique - Saleh, Nursyahirah Mohd (Universiti Sains Malaysia, 2022)
Geological observation is important to characterize the rock mass before classified it into the suitable rock mass classification grade. Traditional way of measuring orientation using geological compass show difficulty in obtaining the result as the worker is exposed to the risk of rock fall. Moreover, the complexity of the tunnel face can produce different results of the face mapping between the geologists. In this study, close range photogrammetry is used to create 3D point cloud. The 3D point cloud is exported to the CloudCompare to obtain facet with the same orientation. The result of the orientation using compass plugin is verify with the orientation obtained using geological compass. Number of photos, number of GCPs (Ground Control Points), setting of the quality, brightness and colour temperature of the light source is the important criteria in creating higher density of the point cloud, less time of analysis and show the correct orientation of the discontinuity on the tunnel face. The optimum and minimum parameter is then taken into consideration in real-life project as it can affect the time and cost of the during tunnelling excavation.